2016
DOI: 10.1007/978-3-319-19680-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Theory for Cubic Graphs

Abstract: We propose a partitioning of the set of unlabelled, connected cubic graphs into two disjoint subsets named genes and descendants, where the cardinality of the descendants is much larger than that of the genes. The key distinction between the two subsets is the presence of special edge cut sets, called crackers, in the descendants. We show that every descendant can be created by starting from a finite set of genes, and introducing the required crackers by special breeding operations. We prove that it is always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…If an edge which is predicted to be n-cracker is omitted, but in fact it does not make a graph is not connected, then still it is named as common cutset. N-cracker only applies on Cubic Graph [5].…”
Section: O N-crackermentioning
confidence: 99%
See 3 more Smart Citations
“…If an edge which is predicted to be n-cracker is omitted, but in fact it does not make a graph is not connected, then still it is named as common cutset. N-cracker only applies on Cubic Graph [5].…”
Section: O N-crackermentioning
confidence: 99%
“…An n-cracker with n ∈ {1, 2, 3} is called cubic cracker. Moreover, if a Cubic Graph does not have any cubic cracker then that graph is called gene [5]. …”
Section: P Genementioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the structures that we search for are those that identify "brittle points" in the graph. Recently, in Baniasadi et al [2,3], it was demonstrated that the set of all connected cubic graphs can be separated into two disjoint subsets, namely genes and descendants. The key distinction between these two subsets is the presence (or absence) of special edge cut sets known as cubic crackers.…”
Section: Introductionmentioning
confidence: 99%